Predictive Factors in OCT Analysis for Visual Outcome in Exudative AMD - Maria-Andreea Gamulescu; Georgios Panagakis; Carmen Theek; Horst Helbig (Journal of Ophthalmology)
Background. Reliable predictive factors for therapy outcome may enable treating physicians to counsel their patients more efficiently concerning probability of improvement or time point of discontinuation of a certain therapy. Methods. This is a retrospective analysis of 87 patients with exudative age-related macular degeneration who received three monthly intravitreal ranibizumab injections. Visual acuity before initiation of intravitreal therapy and 4–6 weeks after last intravitreal injection was compared and related to the preoperative visualisation of continuity of the outer retinal layers as assessed by OCT: external limiting membrane (ELM), inner photoreceptor segments (IPS), junction between inner and outer segments (IS/OS), and outer photoreceptor segments (OPS). Results. Visual acuity increased in 40 of 87 (46.0%) patients, it remained stable in 25 (28.7%), and 22 (25.3%) patients had decreased visual acuity four to six weeks after triple intravitreal ranibizumab injections. No statistically significant predictive value could be demonstrated for grade of continuity of outer retinal layers concerning visual acuity development. Conclusions. In our series of AMD patients, grade of continuity of outer retinal layers was not a significant predictive value for visual acuity development after triple ranibizumab injections.